Convective Heat Pump Dryers and Evaluation of Their Efficiency - M.R., Nazarov; M.I., Daminov; N.M., Nazarova; J., Kuchkarov (RA Journal of Applied Research, 2021)
The article is committed to surveys of drying agrarian products using heat pump dryers; it highlights the most issues of energy saving in thermal and solar dryers. Also in this work, the issues of the application of different strategies of utilizing the heat of the squander drying agent amid convective drying of products are analyzed. Provides important data on the issue of developing energy-saving solar dryers using heat pumps, which is able, diminish energy consumption for drying fruits and vegetables and get high-quality dried products.